2015
DOI: 10.1111/ajt.13105
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Endovascular Management of Transplant Renal Artery Stenosis

Abstract: In this study we analyze the different types of endovascular interventions (EVIs) in de novo transplant renal artery stenosis (TRAS) and its anatomical subtypes to examine any variation in recovery of allograft function, blood pressure control, EVI patency and allograft survival with respect to EVI type (DES: drug-eluting stent, BMS: bare-metal stent, PTA: percutaneous transluminal angioplasty). Forty-five patients underwent a total of 50 primary EVIs (DES: 18, BMS: 26, PTA: 6). Patients were stratified accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 33 publications
3
28
0
Order By: Relevance
“…12 The use of DES in that population was supported by the high rate of restenosis (40-50%) seen when bare metal stents (BMS) were used in small native renal vessels. 13,14 Recently, a similar approach of using DES, BMS and PTA based on clinical parameters was confirmed to have positive short term clinical outcomes. 15 Currently, we present our long-term clinical and procedural outcomes on 57 patients with clinically significant TRAS, using DES for vessel diameters of 5 mm or less and BMS for vessel diameters greater than 5 mm.…”
mentioning
confidence: 97%
“…12 The use of DES in that population was supported by the high rate of restenosis (40-50%) seen when bare metal stents (BMS) were used in small native renal vessels. 13,14 Recently, a similar approach of using DES, BMS and PTA based on clinical parameters was confirmed to have positive short term clinical outcomes. 15 Currently, we present our long-term clinical and procedural outcomes on 57 patients with clinically significant TRAS, using DES for vessel diameters of 5 mm or less and BMS for vessel diameters greater than 5 mm.…”
mentioning
confidence: 97%
“…However, they noted that no consensus existed for the appropriate intervention [3]. Biederman et al compared drug eluting stents and bare metal stents in endovascular balloon dilation on 45 patients, and indicated that long term outcomes of drug eluting stents were superior [7]. In our patient the stenotic segment was widened by 90%, and ascites and hypertension completely resolved.…”
Section: Discussionmentioning
confidence: 68%
“…However, the narrowing of more than 70% is generally symptomatic, and leads to refractory hypertension [7]. Our patient had resistant hypertension and asciImage 1.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations